Efficient and scalable data structures and algorithms for goal-oriented adaptivity of space–time FEM codes - Köcher, Uwe; Bruchhäuser, Marius Paul; Bause, Markus (SoftwareX, 2019)
The cost- and memory-efficient finite element simulation of multi-physics problems remains a challenging task. Goal-oriented space and time adaptive methods derived from the dual weighted residual method appear to be a shiny key technology. They offer to generate optimal sequences of space–time meshes to minimise costs. This work contributes to the efficient embedding of space–time adaptive methods in an application free way for numerical screening tools. A new approach of flexible data structures and algorithms on them is introduced with the provided software dwr-diffusion of the DTM++.Project.